Protocol and Evaluation of Network Mobility with Producer Nodes in Named Data Networking - Lee, Chee Hang; Leau, Yu-Beng; Yong Jin Park; Zhiwei Yan; Supriyanto Praptodiyono (National Dong Hwa University, 2022)
The drawbacks of the current TCP/IP suits have been pointed out. However, Named Data Networking (NDN) has some limitations, the most notable of which is producer and network mobility. Mainly, producer mobility in moving networks receives scant attention. There are numerous issues that the NDN must address before it can be used by the public, one of which is mobility. In NDN, consumer mobility is naturally supported, but producer mobility is not. The latter is researched a lot, but few results have been reported regarding network mobility with producers. In this paper, two approaches will be focused on: The Hybrid Network Mobility (Hybrid NeMo) approach and the Network Mobility (NeMoI). These two approaches are being compared because they both employed similar techniques for managing network mobility. Furthermore, they will be compared using the same topology to allow more accurate comparisons of their signaling cost and data delivery cost.